Mechanism and control of slope instability slip induced by overburden migration in side coal mining - Junpeng LI; Wencai WANG; Chuangye WANG; Xiangye WU (Meitan kexue jishu)
Due to multiple factors, open pit mining will form a large amount of trapped coal on the side wall. With the end of internal discharge and reclamation, these trapped resources will be permanently lost, resulting in great waste. In order to reduce resource waste, shaft mining is widely used, but due to the typical deformation, failure and instability of slope, it brings great safety risks to the mining on the side wall and seriously restricts the recovery of resources. Therefore, it is an important topic for geotechnical engineering and mining engineering to clarify the sliding mechanism and control mechanism of mining slope under mining disturbance and guarantee the stability of slope. In view of this, this paper comprehensively uses physical and numerical simulation, mechanical analysis and other means to study the overburden migration law, the deformation and failure characteristics of mining slope, the instability sliding mechanism and its control mechanism. The following innovative results have been achieved: The evolution law and formation mechanism of the failure form in the “transverse three zones” of the mining slope are revealed, and the relationship between the failure and the coupling failure and instability slip of the mining slope is clarified, and the phenomenon of “circular arc” sliding surface, shear slip zone and local instability slip of the slope is easily caused by mining in the lower coal seam. The co-existent failure characteristics of step collapse and tensile and shear crack of mining slope are obtained. A mechanical model of “masonry beam” of mining slope was established, and the dynamic evolution of “masonry beam” and the relationship between the rotation mechanism of key rock B and the instability and sliding of mining slope were revealed. It is found that the main reasons for the sliding of mining slope are the repeated movement of the “masonry beam” structure, the continuous forward movement of the “transverse three zones” structure, the horizontal thrust formed by the key block B's instability, and the sliding mechanism of “mining cave-bedding creep−slope instability”. The control method of mining slope instability slip for controlling the rotation of key rock block B of “masonry beam” is proposed and analyzed. It is concluded that the backfill pressure foot control method can effectively change the fracture degree of hinged rock block and inhibit the rotation of key rock block B on the basis of curbing horizontal thrust transmission, and achieve the effective control of mining slope instability slip. Based on this, the engineering application and verification are carried out, and the stability control system of mining slope is formed, which provides guarantee for the safe and efficient recovery of side coal.